DEVELOPMENT OF AN IN-SITU FLUID PRESSURE MEASUREMENT DEVICE FOR IN VITRO COMPUTATIONAL FLOW SIMULATION EVALUATION IN VESSELS - Fawwaz Anshori, Hadyan
Intravascular therapy is one of the minimally invasive procedures to address abnormalities in blood vessels. This procedure requires accurate and precise measurements to obtain physical parameters of blood flow. Due to the complexity of the human circulatory system, one effort to predict body hemodynamics is through flow modeling. Research on flow modeling in human vessels using computational fluid dynamics (CFD) has been widely conducted. However, this modeling needs to be validated with an evaluation device to ensure that the simulation results can represent the actual condition of blood vessels. To meet this need, this final project research focuses on the development of an evaluation device for flow in a minimally invasive physical model of blood vessels that can represent the hemodynamic conditions of a stenotic vessel. In silico fluid simulation using computational fluid dynamics (CFD) is conducted to determine the flow conditions in the model based on predefined parameters. The physical model of the blood vessel, which is an ideal approach to the vessel, is fabricated using an additive manufacturing method with resin material. The in vitro measurement device used in this research is a pressure measurement system with the LPS33HWS sensor placed at several points to measure the physical parameters of the flow at specific times. In this final project, a system capable of measuring fluid pressure in a stenotic blood vessel model has been successfully developed. The measurement device has been able to obtain the pressure profile in the vessel model, although further development is needed to improve its accuracy and precision. Keywords: hemodynamics, CFD, flow simulator, additive manufacturing